1990
DOI: 10.1111/j.1600-0773.1990.tb00799.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age and Antiepileptic Drugs on Plasma Levels and Kinetics of Clobazam and N‐Desmethylclobazam

Abstract: The authors monitored the plasma levels of clobazam (CLO) and its principal metabolite, N-desmethylclobazam (NCLO) during chronic treatment of more than 400 epileptic patients receiving different co-medications, such as phenytoin (PH), carbamazepine (CBZ), sodium valproate (VPA) and phenobarbital (PB). This study investigated the influence of age and antiepileptic drugs on plasma levels of CLO and NCLO. Plasma concentrations measured 3 hr after morning administration of CLO varied from 30 to 700 [formula; see … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
2
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 12 publications
0
35
2
1
Order By: Relevance
“…In the same study, the half-life of N-CLB was significantly longer: 49 hours for adults with epilepsy and 57 hours for healthy volunteers. [24] Additional studies were recently conducted that used techniques based on current FDA guidance for these analyses to confirm the pharmacokinetic differences between clobazam and N-CLB. In these studies, clobazam demonstrated a rapid yet moderately variable oral absorption following a single 10 mg dose, with a median time to maximum plasma concentration (t max ) of 1.0 hours (42% coefficient of variation [CV]) and a range of 0.5-2.6 hours.…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same study, the half-life of N-CLB was significantly longer: 49 hours for adults with epilepsy and 57 hours for healthy volunteers. [24] Additional studies were recently conducted that used techniques based on current FDA guidance for these analyses to confirm the pharmacokinetic differences between clobazam and N-CLB. In these studies, clobazam demonstrated a rapid yet moderately variable oral absorption following a single 10 mg dose, with a median time to maximum plasma concentration (t max ) of 1.0 hours (42% coefficient of variation [CV]) and a range of 0.5-2.6 hours.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…[22] Both clobazam and its active metabolite, N-desmethylclobazam (N-CLB), are metabolized in the liver via cytochrome P450 (CYP), primarily 2C19. [23] A 1990 report by Bun et al [24] evaluated the influence of age on clobazam pharmacokinetics in 17 patients with epilepsy (age range: 6-32 years) and 6 healthy volunteers (age range: 24-29 years). The half-life of clobazam was found to be shorter for patients with epilepsy (12 hours for adults and 16 hours for children with epilepsy), compared with 24 hours for healthy volunteers.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…It has previously been suggested that both CLB and NCLB C/D ratios are lower in children, 28 reflecting higher clearance. Some mechanisms thought to lead to increased drug clearance in children (such as increased blood flow) would affect both metabolic steps equally.…”
Section: Impact Of Agementioning
confidence: 98%
“…1) [1]. Moreover, NDCLB is accumulated during long-term treatment achieving concentration levels up to 10-times greater than clobazam and therefore it may be an important factor in both therapeutic and toxic responses [1,5,6].…”
Section: Introductionmentioning
confidence: 98%